A comparison of forces acting on the horse`s back and the stability of the rider`s seat in different positions at the trot - Peham, C.; Kotschwar, A. B.; Borkenhagen, B.; Kuhnke, S.; Molsner, J.; Baltacis, A. (The Veterinary Journal, 2010)
The aim of the study was to compare the stability of the rider as well as the forces acting on a horse`s back with different seating positions at the trot (sitting trot, rising trot and two-point seat). The same experienced rider was mounted on 10 sound horses trotting on a treadmill. The kinetic data were recorded with an electronic pressure mat, placed under a well-fitting dressage saddle with no saddle pad. The rider used three different seating positions, each for 20 s. Right forelimb motion was used to synchronise the pressure data with the stride cycles. To determine the rider`s stability, the movement of the centre of pressure (COP) along the transverse (X) and longitudinal (Y) axes was calculated. The force was taken as the sum of all segments of the pressure pad multiplied by the area of the pressure pad. The maximum force and the X- and Y-deviations were evaluated using ANOVA for repeated measures with a Bonferroni Post hoc test. The stability of the rider in the Y-direction was significantly highest in the two-point seat, followed by the rising trot and the sitting trot, respectively. In the X-direction, there was no significant difference between the three positions. The significantly highest load on the horse`s back was at the sitting trot (2112 N), followed by the rising trot (2056 N) and the two-point seat (1688 N). The rider was most stable in the two-point seat while transferring the lowest load on the horse`s back. The rising trot was found to be more stable and less stressful for the horse`s back compared to the sitting trot.